Optimalisasi Manajemen Kurikulum Dalam Meningkatkan Mutu Pembelajaran di Sekolah Menengah Atas (SMA) Bengkulu - Muhammad Shidiq; Vera Nopianti; Kardiyo Kardiyo (UIN Fatmawati Sukarno Bengkulu, 2023)
Abstract: Curriculum management still creates difficulties among teachers, resulting in the quality of learning still not being optimal, indicated by the fact that there are still teachers who are weak in curriculum development, such as developing learning methods and models which are still not yet complete.optimal. The aim of the research is to determine the optimization of curriculum management in improving the quality of education. Using descriptive qualitative methods. Data collection techniques through observation, interviews and documentation studies. The research results show that: (1) Curriculum management at Bengkulu Senior High School (SMA) has carried out planning, organizing, implementing,based on predetermined plans, have implemented learning evaluation, so that the level of learning quality can be known; (2) Quality of learning in Senior High Schools (SMA) in Bengkulu; (3) Optimizing curriculum management can improve the quality of learning in Senior High Schools (SMA) in Bengkulu. So it can be concluded that curriculum management can improve the quality of learning. Thus, it can be suggested that if you want to improve the quality of learning, improve curriculum management in schools.Keywords: Optimization,Curriculum Management and Learning Quality. Abstrak: Manajemen kurikulum masih menciptakan kesulitan di kalangan guru, sehingga mengakibatkan mutu pembelajaran masih belum optimal, ditandai dengan masih ada guru lemah dalam pengembangan kurikulum seperti pengembangan metode dan model pembelajaran masih belum optimal. Tujuan penelitian untuk mengetahui Optimalisasi manajemen kurikulum dalam meningkatkan mutu pendidikan.Menggunakan metode kualitatif deskriptif. Teknik pengumpulan data melalui observasi, wawancara, dan studi dokumentasi. Hasil penelitian menunjukkan bahwa: (1) Manajemen kurikulum di Sekolah Menengah Atas (SMA) Bengkulu telah dilaksanakan perencanaan ,Pengorganisasian, Pelakasanaan, yang berpedoman pada perencanaan yang telah ditetapkan, telah melaksanakan evaluasi pembelajaran, sehingga dapat diketahui tingkat mutu pembelajaran; (2) Mutu pembelajaran di Sekolah Menengah Atas (SMA) di Bengkulu; (3) Optimalisasi manajemen kurikulum dapat meningkatkan mutu pembelajaran di Sekolah Menengah Atas (SMA) di Bengkulu. Sehingga dapat disimpulkan bahwa manajemen kurikulum dapat meningkatkan mutu pembelajaran. Dengan demikian dapat disarankan jika ingin meningkatkan mutu pembelajaran, maka tingkatkan manajemen kurikulum di sekolah.Kata Kunci: Optimalisasi, Manajemen Kurikulum dan Mutu Pembelajaran